Effect of wind speed and direction on facade fire spread in an isolated rectangular building. (May 2022) - Abu-Zidan, Yousef; Rathnayaka, Shyanaka; Mendis, Priyan; Nguyen, Kate
Abstract: This paper investigates the influence of wind speed and direction on external fire spread in an isolated rectangular building using computational fluid dynamics models validated with wind tunnel data and facade fire tests. Two wind speeds (2 m/s, 4 m/s) are considered for each of four wind directions (0°, 45°, 90°, 180°) and compared to a reference case of no wind. Results indicate that facade fire spread is heavily influenced by the near-wall flow fields generated by the building geometry. These flow fields explain counterintuitive findings such as the upstream tilting of flames under the influence of reverse flow near the side walls. The presence of external wind was found to inhibit the initial development of facade fires, but can greatly exacerbate fire spread once the fire has fully developed. The largest fire occurred for the case of no wind (7.5 GJ in 15 min) while the smallest fire occurred for the 4 m/s diagonal wind case (2.2 GJ). An additional case with temporally varying wind conditions demonstrated a 50% increase in fire spread area compared to no wind. The study provides valuable insight into wind and fire interaction in building facades that can help improve fire safety of buildings. Graphical abstract: Image 1 Highlights: First systematic investigation of its kind into effects of wind on facade fires. Near-wall wind flow field of building dictates behaviour of external fire spread. External wind can greatly increase facade fire spread once fire has fully developed. Variable wind conditions can contribute to reduced fire safety of building facades.